Serum levels of the cold stress hormones FGF21 and GDF-15 after cardiac arrest in infants and children enrolled in single center therapeutic hypothermia clinical trials. (March 2022) - Herrmann, Jeremy R.; Fink, Ericka L.; Fabio, Anthony; Au, Alicia K.; Berger, Rachel P.; Janesko-Feldman, Keri; Clark, Robert S.B.; Kochanek, Patrick M.; Jackson, Travis C.
Abstract: Objective: Fibroblast Growth Factor 21 (FGF21) and Growth Differentiation Factor-15 (GDF-15) are putative neuroprotective cold stress hormones (CSHs) provoked by cold exposure that may be age-dependent. We sought to characterize serum FGF21 and GDF-15 levels in pediatric cardiac arrest (CA) patients and their association with use of therapeutic hypothermia (TH). Methods: Secondary analysis of serum samples from clinical trials. We measured FGF21 and GDF-15 levels in pediatric patients post-CA and compared levels to both pediatric intensive care (PICU) and healthy controls. Post-CA, we compared normothermia (NT) vs TH (33 °C for 72 h) treated cohorts at < 24 h, 24 h, 48 h, 72 h, and examined the change in CSHs over 72 h. We also assessed association between hospital mortality and initial levels. Results: We assessed 144 samples from 68 patients (27 CA [14 TH, 13 NT], 9 PICU and 32 healthy controls). Median initial FGF21 levels were higher post-CA vs. healthy controls (392 vs. 40 pg/mL, respectively, P < 0.001). Median GDF-15 levels were higher post-CA vs. healthy controls (7, 089 vs. 396 pg/mL, respectively, P < 0.001). In the CA group, the median change in FGF21 from PICU day 1–3 (after 72 h of temperature control), was higher in TH vs. NT (231 vs. –20 pg/mL, respectively, P < 0.05), with no difference in GDF-15 over time. Serum GDF-15 levels were higher in CA patients that died vs. survived (19, 450 vs. 5, 337 pg/mL, respectively, P < 0.05), whereas serum FGF21 levels were not associated with mortality. Conclusion: Serum levels of FGF21 and GDF-15 increased after pediatric CA, and FGF21 appears to be augmented by TH.